Who really leads development? - Matt Andrews (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Leadership' is not a common topic for research in international development. In recent years, however, prominent studies like the 2008 Growth Commission Report noted the importance of leadership in development. This and other studies focused on individual leaders - or heroes - when examining 'who leads development'. The current article asks if heroes really do lead development. It deconstructs the implied theory behind the 'hero orthodoxy' into four hypotheses: about how change happens in development; who leads it; how it emerges; and how it is bought to completion. Through a qualitative study of twelve interventions in contexts like Afghanistan, Sierra Leone, and Kosovo, the article shows that these hypotheses are too simple to really help explain who leads development. It appears that change is complex and requires similarly complex multi-agent leadership interventions - not individual heroes.
Keywords: H11; O10; O19; 330; development; leadership; reform; growth; governance; leadership; reform